Pengembangan Materi Ajar Teks Berita Berbantuan Aplikasi Capcut Kelas VII SMP Swasta Al Musabbihin - Ayu Aldina Afriyanti (Simpati, 2024)
This research aims to, (1) describe the process of developing news text teaching materials based on the Capcut application, (2) describe the form of developing news text teaching materials based on the Capcut application, and (3) describe the feasibility of news text teaching materials based on the Capcut application. Developing news text teaching materials based on the Capcut application using ADDIE, with 5 stages, namely analysis, design, development, implementation and evaluation. The news text teaching material product assisted by the Capcut application was validated by including material expert lecturers and expert lecturers. The sample for this research was 27 students in class VII B of Al-Musabbihin Private Middle School using the Purposive Sample technique. Data collection techniques using interviews and questionnaires. The research instrument was a validation questionnaire sheet for material experts and media experts using Likert scale calculations. Data analysis uses qualitative descriptive analysis. Research shows that products from news text teaching materials based on the Capcut application received research results with the criteria "Very Good" with an average of 90.5%, with results from material experts at 90% with the criteria "Very Good" and results from design experts at 91 % with "Very Good" criteria so that teaching materials are suitable for use in the learning process. The product trial results received an assessment from teachers of 95% with the criteria "Very Good" and a student assessment of 92% with the criteria "Very Good".